Electrical-field activated sintering and forming of micro-components - Zulkipli, Muhammad (2017)
As the demand for miniature products has increased significantly, so also has the need for these products to be produced in a rapid, flexible and cost efficient manner. The application of electroplasticity shows significant potential to produce the components by using powder materials. Nevertheless, previous research has shown that there are still significant challenges to be met in order to achieve increased relative densification of product samples and simplification of the processes. The process concept in this study comprises the combination of electrical-field activated sintering and forming processes. Therefore, the aims of the research were to develop the process concept for the manufacture of micro-components and to design the die sets along with other tooling for machine setup to enable the forming of micro-components from powder materials. A comprehensive literature review on micro-manufacturing, size effects, powder metallurgy and the electroplasticity process has been conducted. The development of the die sets for the process has been described, followed by a series of experiments. The FE thermal-electrical analysis was also carried out to study the heating flows of the die sets development during the process. In this research, titanium (Ti) and titanium tin alloy (90Ti10Sn) have been selected for the main powder materials tested for both vacuum and open-air process environment by using a Gleeble® 3800 testing system and Projection Welding machine respectively. Meanwhile, for the additional experiment, copper (Cu) has been selected to be tested in the open-air process environment by using a Projection Welding machine with die sets prepared by the Micro-FAST project. Based on the data collected, this efficient process has the potential to produce components with a high relative density of around 98%. Changes of the particles concerning deformation and breaking are crucial in the course of achieving the densification which differs from a conventional sintering process.